Monocyte MicroRNA Expression in Active Systemic Juvenile Idiopathic Arthritis Implicates MicroRNA‐125a‐5p in Polarized Monocyte Phenotypes. Issue 9 (25th August 2016) - Schulert, Grant S.; Fall, Ndate; Harley, John B.; Shen, Nan; Lovell, Daniel J.; Thornton, Sherry; Grom, Alexei A.
Abstract : Objective: Systemic juvenile idiopathic arthritis (JIA) is an inflammatory disease of childhood in which cells of the monomyelocytoid lineage are thought to be key effector cells. Monocytes from patients with systemic JIA have a distinct phenotype, with features of both M1 and M2 alternative activation. MicroRNAs are critical regulators of monocyte polarization and function, but cellular microRNAs in systemic JIA have not been examined systematically. Methods: MicroRNA TaqMan arrays were used to determine the expression profiles of monocytes from children with systemic JIA. Expression of microRNA‐125a‐5p (miR‐125a‐5p) and its contribution to monocyte polarization were examined using in vitro–polarized THP‐1 cells and primary human monocytes. Results: A total of 110 microRNAs were found to be differentially expressed in monocytes from patients with active systemic JIA, including molecules implicated in rheumatoid arthritis pathogenesis, cytokine production, and monocyte polarization. MicroRNA‐125a‐5p was identified as being highly up‐regulated in monocytes from children with active systemic JIA, as compared to those from children with clinically inactive JIA or those with active polyarticular JIA, and correlated with systemic features of the disease. In vitro, monocyte miR125a‐5p expression was increased after polarization under M2b or M2c conditions. Inhibition of miR‐125a‐5p showed that this microRNA contributed to full polarization of M2b regulatory macrophages. In contrast, miR‐125a‐5p overexpression enhanced M2b polarization and altered other polarized populations, including increasing the production of M2 markers. Indeed, in vitro overexpression of this microRNA altered the macrophage phenotype toward that observed in systemic JIA. Conclusion: Children with active systemic JIA have profound alterations in the expression of microRNAs that are implicated in monocyte function and polarization. One of these microRNAs, miR‐125a‐5p, is also a regulator of immunoregulatory M2b macrophages.